Intertextuality in Paljetak's 'After Hamlet' - Gjurgjan, Ljiljana Ina (Array, 1999)
After Hamlet is a post-modern reinscription of Shakespeare's play. It points to instability of knowledge and memory thus rendering Hamlet's sacrifice as absurd. The play reflects the attitude towards Europe and its cultural heritage at a time of the siege of Dubrovnik.